Value-added application of Platycodon grandiflorus (Jacq.) A.DC. roots (PGR) by ultrasound-assisted extraction (UAE) process to improve physicochemical quality, structural characteristics and functional properties. (30th November 2021) - Liu, Yuan-yuan; Sun, Wei-hong; Li, Bing-zheng; Shang, Nan; Wang, Yong; Lv, Wei-qiao; Li, Dong; Wang, Li-jun
Highlights: Platycodon grandiflorus (Jacq.) A.DC. root (PGR) powder rich in bioactive compounds was obtained. Ultrasound-assisted extraction (UAE) increased the powder recovery of PGR powder. UAE enhanced bioactive compounds content and antioxidant activity of PGR powders. PGR powders are thermally stable under process temperature lower than 120 °C. UAE-FD PGR powders maintained its nutritional value with better hydration property. Abstract: Platycodon grandiflorus (Jacq.) A.DC. roots (PGR), a Chinese herb with medicinal and edible value, was powdered by freeze drying (FD) and spray drying (SD) after maceration extraction (ME) or ultrasound-assisted extraction (UAE) to develop a new functional food product. Four PGR powders were obtained namely ME-FD, ME-SD, UAE-FD, and UAE-SD and their powder quality, structural properties, and functionalities were evaluated. UAE-FD powder had the highest powder recovery (85.3 ± 5.79%) and also presented better hydration properties due to the larger particle size compared with other three PGR powders. Four PGR powders exhibited similar thermal decomposition process, molecular structure, amorphous characteristics, amino acids composition, and taste profiles. Furthermore, the UAE-FD PGR powders presented the highest Platycodin D (3.68 ± 0.04 mg/g), total phenolic (2.84 ± 0.11 mg GAE/g), and total flavonoids content (2.11 ± 0.14 mg RE/g), resulting in best antioxidant activity (58.67 ± 2.42 μmol Trolox/g). Therefore UAE-FD is an environment-friendly technique for the production of functional PGR powder with improved nutritional and redispersion properties.